The Effect of Communication, Work Environment, and Conflict Management on Performance - Erika Ambarita; Trifiana Tiodora; Innocentius Bernarto (Enrichment : Journal of Management, 2020)
This study aims to determine the effect of communication, work environment, and conflict management on the performance of English teachers in public and private high schools in West Jakarta I. The data used in this study are primary data by distributing questionnaires to 40 respondents using census techniques. The analysis model used is multiple linear regression using the SPSS 24.0 analysis tool. The results showed that communication had a positive and significant effect on the performance of English teachers in public and private high schools in West Jakarta I. The work environment had a positive but insignificant effect on the performance of English teachers in public and private high schools in West Jakarta I. Conflict management had a positive and significant effect on performance. English teachers at public and private high schools in West Jakarta I. Communication, work environment, and conflict management have a positive and significant effect on the performance of English teachers in public and private high schools in West Jakarta I.